Pengembangan Alat Evaluasi Berbasis Three Tier Multiple Choice Menggunakan Wondershare Quiz Creator untuk Mengidentifikasi Miskonsepsi - Nanda Eka Damayanti; Irwani Zawawi; Fatimatul Khikmiyah (Postulat : Jurnal Inovasi Pendidikan Matematika, 2021)
Evaluation can be used to measure the understanding of students' concepts in geometry material. However, there are still many students who have difficulty in understanding the concept of geometry. This often leads to misconceptions. An effort to identify misconceptions is to conduct a three-tier multiple choice-based evaluation test. Evaluation can take advantage of online question maker technology such as the Wondershare Quiz Creator application. The purpose of this research is to develop a three tier multiple choice based evaluation tool using wondershare quiz creator to identify misconceptions that can be used online. The development research model uses the 4D model. The research subjects were students of class VII-A SMPN 5 Lamongan. The research instruments used were interview sheets, validation sheets, test instruments, and questionnaires. The data analysis technique used qualitative and quantitative analysis. The result of the research is an evaluation tool based on three tier multiple choice using wondershare quiz creator to identify misconceptions as seen from: (1) the appropriateness of the evaluation tool meets the valid and effective criteria which reaches more than 60%. As well as with the statistical tests carried out, the instrument has met the criteria given so that the evaluation tool can be used. (2) Types of misconceptions consist of classification misconceptions, correlational misconceptions, and theoretical misconceptions. Of the three types of misconceptions, students experienced the most misconceptions at level 2, namely answering incorrect choice of reasons.